Developing a culturally-relevant public relations theory for Indonesia - Kriyantono, Rachmat; Mckenna, Bernard (Penerbit Universiti Kebangsaan Malaysia, 2017)
The article views public relations study and practice from an Indonesian perspective. As an applied communication science, public relations has been dominated by Western perspective. However, the idea of the need to study communication from the Eastern (including Indonesian) perspective has emerged recently. Some public relations theories from a Western perspective may need to be applied differently because of the difference of societal systems and philosophical backgrounds. There are Indonesian philosophical beliefs that should underpin public relations in Indonesia. On the other hand, there is no single theory comes from Indonesian perspective due to lack of local wisdoms exploration as a basic to build communication theories relevant with Indonesian contexts. The aim of the article is to stimulate the development of public relations theories by adopting Indonesian local wisdom, Indonesia-West theoretical collaboration, and critical reflection on Western theory. The authors has explored some Indonesian’s proverbs that represent Indonesian local wisdoms to search for similarities and differences between Western and Indonesian perspectives. The authors present a normative Indonesian perspective as a basis for future public relations theory building in Indonesian context. The cultures, traditions, and moral norms of a country can be maintained even though the country may be undergoing rapid transformation towards a more Western economy and lifestyle.